Effectiveness of family metacognitive training in mothers with psychosis and their adolescent children: a multicenter study protocol - Ochoa, Susana; Espinosa, Victoria; López-Carrilero, Raquel; Martinez, Irene; Barrera, Alejandro De Haro; Birulés, Irene; Barajas, Ana; Pélaez, Trinidad; Díaz-Cutraro, Luciana; Coromina, Marta; González-Rodríguez, Alexandre; Verdaguer-Rodríguez, Marina; et al. (Frontiers in Psychology, 2024)
Background: More than half of women with psychosis take care of their children despite the difficulties caused by the disease. Additionally, these kids have a higher risk of developing a mental health disorder. However, no interventions have been developed to meet these needs. Metacognitive Training (MCT) is a psychological intervention that has demonstrated its efficacy in improving cognitive insight, symptom management and social cognition in people with first-episode psychosis (FEP). Additionally, MCT has shown better results in women than men with FEP. This study aims to adapt and evaluate the efficacy of MCT-F in mothers and adolescent children in an online group context with the main purpose of improving family relationships, cognitive awareness and symptoms in women with psychosis and increase their children's knowledge of the disease and their functioning. As secondary objectives, it also aims to evaluate improvements in metacognition, social cognition, symptoms, protective factors and self-perception of stigma.A quasi-experimental design with participants acting as their own control will be carried out. Forty-eight mothers with psychosis and their adolescent children (between 12 and 20 years old) recruited from a total of 11 adult mental health care centres will receive MCT-F. Participants will be evaluated 11 weeks before the intervention (T1), at baseline (T2) and postintervention (T3) with a cognitive insight scale, as a primary outcome. Measures of metacognitive and social cognition, symptoms, cognitive functioning, family and social functioning, protective factors (self-esteem, resilience, and coping strategies) and self-perceived stigma will be addressed as secondary outcomes. Assessment will also address trauma and attachment in mothers and, lastly, the feasibility and acceptability of MCT-F in both participant groups.Discussion: This will be the first investigation of the efficacy, acceptability, and viability of the implementation of MCT-F. The results of this study may have clinical implications, contributing to improving mothers' with psychosis and adolescents' functioning and better understanding of the disease, in addition to the possible protective and preventive effect in adolescents, who are known to be at higher risk of developing severe mental disorders.[https://clinicaltrials.gov/], identifier [NCT05358457].